Emma Kate - Polacco, Patricia (New York : Puffin Books, 2008)
Emma Kate and her best friend share many activities, such as homework and soccer practice, and even have their tonsils out at the same time--all the things best friends do, but there is more to this best friend than meets the eye.
School Library Journal.
Publisher's Weekly.
Booklist.
2.0
K-3
2.0.
Keywords: Imaginary companions -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Elephants -- Juvenile fiction; Imagination -- Juvenile fiction; Imaginary playmates -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Elephants -- Fiction; Imagination -- Fiction; Imaginary playmates -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Elephants -- Fiction; Imagination -- Fiction